Wastewater reclamation and reuse in China：Opportunities and challenges - Lyu, Sidan; Chen, Weiping; Zhang, Weiling; Fan, Yupeng; Jiao, Wentao (Journal of environmental sciences (China), 2016)
The growing water stress both in terms of water scarcity and quality deterioration promotes the development of reclaimed water as a new water resource use. This paper reviewed wastewater reuse practices in China, and the opportunities and challenges of expanding reclaimed water use were analyzed. Rapid urbanization with the increasing of water demand and wastewater discharge provides an opportunity for wastewater reuse. The vast amount of wastewater discharge and low reclaimed water production mean that wastewater reuse still has a great potential in China. Many environmental and economic benefits and successful reclamation technologies also provide opportunities for wastewater reuse. In addition, the overall strategy in China is also encouraging for wastewater reuse. In the beginning stage of wastewater reclamation and reuse, there are many significant challenges to expand wastewater reuse in China including slow pace in adopting urban wastewater reuse programs, the establishment of integrated water resources management framework and guidelines for wastewater reuse programs, incoherent water quality requirements, the limited commercial development of reclaimed water and the strengthening of public awareness and cooperation among stakeholders.